تفعيل دور بورصة الأوراق المالية وأثرها على النمو الإقتصادي دراسة -بورصة عمان للأوراق المالية من: 1988 إلى 2013 - غالم, عبد الله; خزان, عبد الحفيظ (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
إن التحولات الإقتصادية التي طرأت على العالم بأكمله صارت تفرض مواكبه ما يحدث من تطورات هيكلية في الإقتصاد العالمي والبحث عن أنسب الطرق لتحقيق النمو الإقتصادي والتنمية، ولعل من أسرع وأعمق ما تم من تحولات تلك التي عرفها الجانب المالي من خلال ظهور مؤسسات مالية تمويلية جديدة تتقدم مع تقدم المشاريع وتكبر لتستوعب ضخامتها ورؤوس أموالها والتي نجد من أهمها بورصة الأوراق المالية . فقد أصبحت هذه الأسواق قوة مالية هامة في العديد من الدول وبالأخص المتقدمة منها وحلقة ضرورية لربط المستثمر ( المقترض ) بالمدخر ( المقرض ) ، وعنصراً هاماً لتأمين السيولة الضرورية للحياة الإقتصادية، وفيما ركزت الدراسات السابقة إلى حد كبير على الدور الإيجابي للبنوك في تحقيق النمو الإقتصادي، فإن هذه الدراسة تضيف مسألة بورصة الأوراق المالية وآثرها على النمو الإقتصادي وتحقيق زيادة في معدلات النمو وبخاصة في الأردن والتي يعاني قطاعها المصرفي من تأخر كبير في الإيفاء بالحاجات التمويلية للنشاط الإقتصادي بها وضعف في الكفاءة التشغيلية والمالية كذلك أعتمادها على نظام المديونية بشكل كبير . ما هو أثر سوق الأوراق المالية لتحقيق معدلات النمو الإقتصادي؟ الكلمات المفتاحية : سوق الأوراق المالية، النمو الإقتصادي، الناتج المحلي الإجمالي . Abstract : Activating the role of the securities markets and their impact on economic growth Study «market Amman Stock Exchange of: 1988 to 2013« The economic transformations that have taken place in the entire world has become impose keep up with what is happening from the structure of the global economic developments and the search for the most appropriate way to achieve economic growth and development, and perhaps one of the fastest and deepest what has been the transformations that defined the financial side through new financing financial institutions advancing with the advent of project progress and grow to accommodate the magnitude and their capital and in which we find the most important stock markets. These markets have become an important financial power in many countries, particularly developed and loop is necessary to connect the investor (the borrower) Saver (lender), and an important element to secure the necessary economic life of liquidity, as previous studies have focused largely on the positive role of banks in achieving economic growth, This study adds the issue of the securities markets and their impact on economic growth and an increase in growth rates, particularly in Jordan and that the banking sector is suffering from a significant delay in the fulfillment of the financing needs of economic activity by weakness in financial and operational efficiency as well as its dependence on debt system significantly. What is the impact of the stock market to achieve economic growth rates? Keywords: Securities markets, Economic growth, Output Local .